Orphans of Islam: Family, Abandonment, and Secret Adoption in Morocco - Bargach, Jamila (Rowman & Littlefield Publishers, 2002)
Orphans of Islam portrays the abject lives and 'excluded body' of abandoned and bastard children in contemporary Morocco, while critiquing the concept and practice of 'adoption,' which too often is considered a panacea. Through a close and historically grounded reading of legal, social, and cultural mechanisms of one predominantly Islamic country, Jamila Bargach shows how 'the surplus bastard body' is created by mainstream society. Written in part from the perspectives of the children and single mothers, intermittently from the view of 'adopting' families, and employing bastardy as a haunting and empowering motif with a potentially subversive edge, this ethnography is composed as an intricate, open-ended, and arabesque-like evocation of Moroccan society and its state institutions. It equally challenges received sociological and anthropological tropes and understandings of the Arab world.